The Road Less Travelled: Female Principalship in Western Australia - Russell, Leanne Dawn (Curtin University, 2023)
This qualitative interpretative study seeks to answer why there are not more female secondary school principals in Western Australia. Interviews with women leaders employed within secondary government and independent private schools has resulted in the development of the Road to Leadership matrix to provide a guide to key success factors for women aspiring to principal roles and to provide advice to organisations seeking to increase the number of women in leadership.